DETERMINAN SUKU BUNGA DASAR KREDIT (SBDK) SEKTOR KORPORASI PADA BANK BUKU 4 - Budi Santosa; Erny Tajib; Jihad Ihsan Ramadan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the factors that determine the Prime lending Rate (SBDK) in the Corporate Sector at Bank BUKU 4. In this study, the researchers used these variables from seven Book 4 banks for the 2015-2019 Period in the case of the corporate sector prime lending rate. Therefore, this research data is panel data obtained from the Indonesian Banking Statistics (SPI) published by BI. Data processing is carried out using the Econometric Model of Panel Data Regression Analysis and Eviews 9.0 as processing instruments. Based on the results of data processing, it was found that the model used was Fixed Effect with the ability of independent variables (liquidity, capitalization, lending out ratio, credit risk, and efficiency) to be able to explain the dependent variable prime lending rate (SBDK) of 56.05%. However, the regression coefficient shows that only NPL and BOPO have a significant effect on the SBDK. In other words, only the level of bad loans and banking efficiency have a significant effect on the prime lending rate.